ART BLOGGING IN ART JOURNALISM - Abduvakhob Qodirov (International Journal of Literature and Language Studies, 2026)
The rapid digitalization of mass communication has fundamentally transformed the practice of journalism, giving rise to new forms of content production and dissemination. Among these innovations, art blogging has become one of the most influential phenomena within contemporary art journalism. Unlike traditional journalistic formats, art blogs combine professional criticism, visual storytelling, personal reflection, and interactive communication, creating a multidimensional platform for discussing artistic and cultural issues. This article examines the development of art blogging as an integral component of modern art journalism, explores its communicative characteristics and social significance, and analyzes its influence on cultural discourse, audience engagement, and digital media practices. Particular attention is paid to the relationship between professional journalism and independent digital content creation, as well as to the role of multimedia technologies in shaping new forms of artistic communication.